2018
DOI: 10.1029/2018ja025749
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Auroral Electron Precipitation Mechanism Combinations and Their Relationships to Net Downgoing Energy and Number Flux

Abstract: We present initial statistical results of a new methodology for identifying electron precipitation mechanisms in Earth's auroral zone. Unlike previous methodologies, it identifies multiple mechanisms observed in the same event, utilizing Fast Auroral Snapshot measurements of upward energy and pitch angle spectra in addition to downward energy spectra. For intense precipitation (peak downgoing differential energy flux >108 eV/cm2‐s‐sr‐eV) our method separately identifies the three main precipitation mechanisms:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 74 publications
(137 reference statements)
5
45
0
Order By: Relevance
“…Such analysis will need to be done in future. And finally, some caution is advised as not all data points in our wave band necessarily represent Alfvén waves (Keiling et al, 2019a), and there is the possibility that the number flux of Alfvénic electrons, and thus their total energy flux, was overestimated by Newell & Gjerloev (2011), which was recently suggested by Dombeck et al (2018). In spite of these uncertainties, which cannot be resolved here, we still find our results mostly consistent, while providing, for the first time, global power estimates for Alfvén waves during different substorm phases above the AAR.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Such analysis will need to be done in future. And finally, some caution is advised as not all data points in our wave band necessarily represent Alfvén waves (Keiling et al, 2019a), and there is the possibility that the number flux of Alfvénic electrons, and thus their total energy flux, was overestimated by Newell & Gjerloev (2011), which was recently suggested by Dombeck et al (2018). In spite of these uncertainties, which cannot be resolved here, we still find our results mostly consistent, while providing, for the first time, global power estimates for Alfvén waves during different substorm phases above the AAR.…”
Section: Discussionmentioning
confidence: 96%
“…For example, Newell et al (2009), using only low‐altitude electron measurements (from DMSP data) to separate auroral precipitation types, suggested that up to 13% of the auroral power (as determined from the entire hemisphere) is likely associated with Alfvén wave acceleration processes during active periods (strong solar wind driving) and up to 6% during quiet conditions (weak solar wind driving). Allowing for the recent objections by Dombeck et al (2018), these values could be higher, because it was argued that the diffuse aurora was potentially significantly overestimated, which would have the effect of lowering the contributions due to the discrete aurora, both quasistatic aurora and Alfvénic aurora. In contrast, Chaston et al (2007), using both Alfvén wave and electron measurements (from FAST data), inferred that with increasing auroral activity, 25% to 39% of electron energy deposition into the hemispheric auroral zone ionosphere, and up to 50% in the premidnight region alone, may be attributed to the driving of Alfvén waves.…”
Section: Discussionmentioning
confidence: 96%
“…It has been a challenge to determine the global contributions of each type to the aurora. Under various geomagnetic conditions (but not storms per se), estimates of Alfvénic aurora range between 6 and 50% of the total aurora ( 33 35 ), with the lower estimate believed to be too low ( 36 ). To what extent the storm aurora is Alfvénic is not known as of yet, and its determination, is outside the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, using only low‐altitude (below the AAR) electron measurements, it was suggested that up to 13% of the auroral power is likely associated with Alfvén wave acceleration processes during active periods (Newell et al, ). However, this estimate could be higher if one accounts for the objections brought forth by Dombeck et al (). Morphological similarities between global Alfvén wave maps and Alfvénic electron maps, as shown in the above studies, further corroborate the Alfvénic coupling scenario.…”
Section: Introductionmentioning
confidence: 85%